Raman imaging of the phycosphere reveals sharp gradients of organic matter exuded by single phytoplankton cells - Zachary C. Landry; Riccardo Foffi; Valerio Anelli; Paolo Arosio; Marcos Gil-García; Richard J. Henshaw; Oliver Müller; Giacomo Paccagnan; Timo N. Schneider; Carsten J. Schubert; Jonasz Słomka; Kang Soo Lee; et al. (Proceedings of the National Academy of Sciences, 2026)
Phytoplankton cells exude a wide array of chemicals in the water column, generating a localized microenvironment known as the phycosphere. Although it is now well accepted that the phycosphere mediates interactions between phytoplankton and bacteria, the chemical gradients around individual phytoplankton cells have never been explicitly measured, and their shape has been classically assumed to be set by ideal diffusion. Here we used Raman microspectroscopy to obtain micrometer-scale measurements of the concentration profile of a phytoplankton metabolite (fucoxanthin) around individual phytoplankton cells of different species, having radii between 2.5 and 60 μ m. We found that fucoxanthin concentration decreases more rapidly with distance from the cell than predicted by ideal diffusion, showing that the phycosphere includes compounds whose diffusion is characterized by nonideal effects. We explain this observation using a space-dependent diffusivity model where nonideality arises from viscosity and solubility gradients in the extracellular environment. Our results suggest an onion-structured model of the phycosphere, in which small hydrophilic solutes that obey ideal diffusion generate broad but weak gradients, whereas insoluble compounds are retained within 10 to 20 μ from the phytoplankton cell surface and yield steep gradients of organic matter. These observations, supported by evidence that fucoxanthin can act as an effective chemoattractant for marine bacteria, show the existence of strong and highly localized chemical cues with potentially far-reaching impacts on microbial interactions in aquatic environments. These findings highlight the importance of directly measuring the microscale chemical landscape experienced by marine microbes.